Learner-Centric Technologies to Support Active Learning Activity Design in New Education Normal: Exploring the Disadvantageous Educational Contexts - Hasnine, Mohammad Nehal; Ahmed, Mahmoud Mohamed Hussien; Ueda, Hiroshi (International Journal of Emerging Technologies in Learning (iJET), 2021)
Active learning is a learner-centric instructional method that uses discussion, role play, collaborative problem-solving based approaches to engage students with the course materials. However, due to the pandemic, active learning activities take place over multiple learner-centric technologies, as classroom-centered activity design is no longer possible. This study explored the success stories of active learning in disadvantageous educational contexts, particularly in Arab regions. After examining the theory, models, various learner-centric technologies of pre-pandemic active learning de-signs, this study proposes 25 emerging technologies to support active learn-ing 19 active learning strategies in terms of activity design in new education normal. The three-fold findings are related to designing active learning activities in new education normal, enhancing less practiced active learning strategies, and bridging the gaps in pre-and post-pandemic active learning activity design using learner-centric technologies.